Striosomal dysfunction affects behavioral adaptation but not impulsivity-Evidence from X-linked dystonia-parkinsonism - Beste, Christian; Mückschel, Moritz; Rosales, Raymond; Domingo, Aloysius; Lee, Lillian; Ng, Arlene; Klein, Christine; Münchau, Alexander (Movement disorders, 2017)
BACKGROUND: Executive functions including behavioral adaptation and impulse control are commonly impaired in movement disorders caused by striatal pathology. However, as yet it is unclear what aspects of behavioral abnormalities are related to pathology in which striatal subcomponent, that is, the matrix and the striosomes. We therefore studied cognitive control in X-linked dystonia-parkinsonism, a model disease of striosomal degeneration, using behavioral paradigms and EEG. METHODS: We studied genetically confirmed X-linked dystonia-parkinsonism patients (N = 21) in their early disease stages and healthy matched controls. Error-related behavioral adaptation was tested in a flanker task and response inhibition in a Go/Nogo paradigm during EEG. We focused on error-related negativity during error processing and the Nogo-N2 and Nogo-P3 in the response inhibition task. Source localization analyses were calculated. In addition, total wavelet power and phase-locking factor reflecting neural synchronization processes in time and frequency across trials were calculated. RESULTS: Error processing and behavioral adaptation predominantly engaging the anterior cingulate cortex was markedly impaired in X-linked dystonia-parkinsonism. This was reflected in abnormal reaction times correlating with error-related negativity amplitudes, error related theta band activity, and the phase-locking factor. Also, abnormal error processing correlated with dystonia severity but not with parkinsonism. Response inhibition and corresponding EEG activity were normal. CONCLUSIONS: This dissociable pattern of cognitive deficits most likely reflects predominant dysfunction of the striosomal compartment and its connections to the anterior cingulate cortex in X-linked dystonia-parkinsonism. The results underscore the importance of striosomes for cognitive function in humans and suggest that striosomes are relays of error-related behavioral adaptation but not inhibitory control. © 2017 International Parkinson and Movement Disorder Society.
Keywords: dospělí; Magnetic Resonance Imaging; Adult; kognitivní poruchy; dystonické poruchy; Genetic Diseases, X-Linked; Impulsive Behavior; Dystonic Disorders; lidé; magnetická rezonanční tomografie; fyziologická adaptace; impulzivní chování; mozek; Cognition Disorders; Male; Brain; genetické nemoci vázané na chromozom X; inhibice (psychologie); Adaptation, Physiological; lidé středního věku; mužské pohlaví; Inhibition, Psychological; elektroencefalografie; Middle Aged; Electroencephalography; Humans